The Effectiveness of Auditory Intellectually Repetition (AIR) on Listening Skill Ability Through Podcasts - Haifa, Haifa; Athena, Tera; Maria Ulfa, Siti (Universitas PGRI Madiun, 2024)
This study investigates the impact of the Auditrory Intellectually Repetition (AIR) learning model implemented through podcasts on Class XI students’ listening skills. The research aims to enhance students’ listening comprehension and engagement, with a focus on the effectiveness of the AIR model. A pre-test was conducted on 28 students in the experimental group to assess their intial listening skills. The results indicated varying levels of proficiency among the students. Following treatment with the AIR learning model through podcasts, a significant improvement in listening comprehension was observed in the comparison of the experimental group with the control group. The findings support the efficacy of the AIR learning model in enhancing students’ listening abilities, aligning with previous research in the field. The study contributes to the existing literature on the importance of listening ability in language education it also underscores the potential benefits of utilizing podcasts for improving listening comprehension.